SmartParents: empowering parents to protect children from cyber threats - Abdul Molok, Nurul Nuha; Abdul Hakim, Nur Aiena Hajeerah; Jamaludin, Nur Syazwani (IIUM Press, 2023)
In today’s interconnected world, parents and children face cyber safety and security issues and are exposed to cyber threats. During and after the COVID-19 pandemic, cyber safety and security cases are on the rise affecting people of all ages. During the movement control orders (MCO), children were given electronic gadgets to participate in online learning. Although there is no MCO and online learning anymore, children are still reliant on these gadgets, affecting their studies, health and safety. This study covers cyber threats that are happening to children and what can parents do about such threats to protect their children. It proposes educating parents about cyber safety and security through a web-based application prototype. Surveys were done to understand the actual cyber threats that were faced by both parents and children in order to collect user requirements for the development of the prototype. Findings suggest that such applications can help parents to recognise cyber threats that can happen to their children. The developed prototype may guide parents to implement cyber safety and security controls and protect their children from cyber threats such as cyberbullying, sexual grooming and gaming disorder.